Age- and Growth-Based Life-History Traits of Striated Surgeonfish (Ctenochaetus striatus) and Achilles Tang (Acanthurus achilles) from Miti‘āro, Cook Islands - Vavia, Antony; Trip, Elizabeth DL; Visconti, Valerio; Lilkendey, Julian; Zhang, Jingjing; Owen, Charlie; Sabetian, Armagan (Wiley, 2026)
Striated surgeonfish (Ctenochaetus striatus) and Achilles tang (Acanthurus achilles) are two surgeonfish species commonly harvested for subsistence on Miti‘āro, Cook Islands. Using individuals collected by local fishers, this study provides the first age- and growth-based assessment of these species from Miti‘āro. Age and size distribution of C. striatus ranged from 1 to 27 years and 105–250 mm (FL), respectively. Age and size distribution of A. achilles ranged from 0 to 9 years and 137–215 mm (FL), respectively. Von Bertalanffy growth function (VBGF) models estimated asymptotic lengths of 185.18 mm for C. striatus and 183.11 mm for A. achilles. Likelihood ratio tests and 95% confidence ellipses of VBGF parameters (L∞ and K) indicated no significant differences in growth between males and females for either species. Length–weight analyses showed C. striatus exhibited slightly negative allometric growth, while A. achilles displayed an isometric relationship. Annual mortality was estimated at ~36% for both species. These findings provide new insights into the life-history and population dynamics of key reef fish targeted for subsistence in the Cook Islands.
Keywords: 04 Earth Sciences; 05 Environmental Sciences; 06 Biological Sciences; Marine Biology & Hydrobiology; 31 Biological sciences; 37 Earth sciences; 41 Environmental sciences